Potensi Bunga Anggrek Cymbidium Golden Boy sebagai Sumber Antioksidan dan Aplikasinya pada Flower Leather - Khoidir, Syntiya Inanda; Irjayanti, Rika Cahyani; Purnama, Annisa Jihan; Wakhidah, Nastiar Majidatun; Anggriani, Rista (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2024)
Orchid flowers are believed to be an antioxidant source, however, the antioxidant activity of the Cymbidium Golden Boy (CGB) orchid has not been identified. The antioxidant potential can be applied to flower leather products, and a main reason behind the idea is the valorization of agricultural waste. The aim of this research is to study phenol content and antioxidant capacity of ethanol extracts of CGB orchid petals. Additionally, this study aimed to determine the best formulation for flower leather products with a combination of carrageenan and gum arabic based on organoleptic acceptance. This research was conducted by extracting CGB orchid flowers using ethanol, and total phenol and antioxidant activity of the extracts were determined. Moreover, the flower leather products were mad from CGB orchid flowers as the raw material, accroding to a Factorial Randomized Block Design using two factors as follows: carrageenan concentration (0, 0.3, 0.5, and 0.7%) and gum arabic concentration (0.9, 1.2, and 1.5%). Flower leather samples were analyzed for moisture content, tensile strength, total dissolved solid, color intensity, and sensory. The ethanol extract of CGB orchid flowers showed antioxidant capacity up to 23.88 ppm and high phenolic content which is equal to 15.32 mg GAE/g. The differences between carrageenan and arabic gum concentration showed significant effect on water content and dissolve solid, but they did not affect on tensile strength and color intensity. The best treatment of flower leather according to panelist evaluation was those prepared from carrageenan 0.5% and arabic gum 0.9%, reaching tensile strength 4.86 N, brightness level (L) 40.1, (a+) +5.7, (+b) 23.7, water content 19.18%, aroma score 3.76 (slight flowery), taste 4.84 (pleasant), and texture 4.56 (approaching chewiness).